Direct electrolysis of waste newspaper for sustainable hydrogen production: an oxygen-functionalized porous carbon anode - Hibino, Takashi; Kobayashi, Kazuyo; Ito, Masaya; Nagao, Masahiro; Fukui, Mai; Teranishi, Shinya (Applied catalysis. B, Environmental, 2018)
[Display omitted] •The carbonyl group-functionalized carbon anode was more active for newspaper oxidation compared to the Pt/C anode.•The electrolysis onset voltage was decreased to ca. 0.2 V.•The current efficiency for hydrogen production was approximately 1.0.•Hydrogen was produced continuously in a current density range of 0.15–0.25 A cm−2.•The energy consumed for hydrogen production at a current density of 0.15 A cm−2 was 1.27 kWh (Nm3)-1. Biomass electrolysis enables hydrogen (H2) production at onset voltages of less than 1 V, depending on the fuel species. However, biofuel derived from biomass not categorized as food and produced from environmentally friendly processes is needed for the development of sustainable strategies. In addition, the biofuel should not require special and expensive procedures for processing. The present report describes the direct electrolysis of waste newspaper for H2 production. Cellulose and lignin included in the newspaper were subject to dissolution and hydrolysis in a phosphoric acid solvent at the anode in a temperature range of 100–175 °C. The resulting decomposition products were electrolyzed to H2 and carbon dioxide (CO2), at low onset voltages (ca. 0.2 V) and high current efficiencies (H2: 1.0, CO2: 0.9). Carbon black functionalized with carbonyl groups showed greater catalytic activity than a Pt/C catalyst for the anode reaction. H2 yield reached ca. 0.2 g per 1 g of newspaper in a batch cell. H2 was produced continuously in a current-density range of 0.15–0.25 A cm−2 while maintaining plateau-like voltage behavior in a flow cell. The energy consumed for electrolysis at a current density of 0.15 A cm−2 was as low as 1.27 kWh (Nm3)−1.